The Effect of Plyometric Training on Increasing Explosive Power in Female Basketball Athletes of Redjay Bekasi - Muhammad Ridhwan; Faiz Akbar Arifin; Aditya Gautama; M. Arief Setiawan; A. Ine Aprilia Damai; Aprillia Wulan Utari (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
The study aimed to analyze the effect of plyometric training on improving the explosive power of female basketball athletes from Redjay Bekasi. The background of the study was based on the importance of lower-limb explosive power in supporting basketball performance, especially in jumping movements, short sprints, changes of direction, and shooting execution. The research employed a quantitative method with a quasi-experimental approach using a one-group pretest-posttest design. The subjects consisted of 18 female basketball athletes aged 15–20 years who actively participated in the team training program. The intervention consisted of an 8-week plyometric training program with a frequency of three sessions per week. The research instruments included the Vertical Jump Test, Standing Broad Jump, 20-Meter Sprint, and T-Test Agility. Data analysis used descriptive statistics, the Shapiro-Wilk normality test, Levene’s Test of homogeneity, and the paired sample t-test for hypothesis testing. The results showed significant improvements in all variables after the intervention. The mean score of the Vertical Jump increased from 39.22 cm to 45.11 cm, the Standing Broad Jump increased from 176.44 cm to 189.67 cm, the 20-Meter Sprint time decreased from 3.74 seconds to 3.52 seconds, and the T-Test Agility time decreased from 11.41 seconds to 10.93 seconds. The results of the paired sample t-test showed a significance value of 0.000 < 0.05 for all variables. The conclusion confirmed that plyometric training had a significant effect on improving explosive power, speed, and agility of female basketball athletes from Redjay Bekasi. The program is appropriate to be implemented as part of the physical conditioning development for female basketball athletes.